Pairwise entanglement and the Mott transition for correlated electrons in nanochains - Adam Rycerz (New Journal of Physics, 2017)
Pairwise entanglement, calculated separately for charge and spin degrees of freedom, is proposed as a ground-state signature of the Mott transition in correlated nanoscopic systems. Utilizing the exact diagonalization— ab initio , for chains containing $N\leqslant 16$ hydrogenic-like atoms (at the half filling), we find that the vanishing of the nearest-neighbor charge concurrence indicates the crossover from a partly-localized quantum liquid to the Mott insulator. Spin concurrence remains nonzero at the insulating phase, showing that the decopling of spin and charge degrees of freedom may manifest itself by wavefunctions entangled in spin, but separable in charge coordinates. At the quarter filling, the analysis for $N\leqslant 20$ shows that spin concurrence vanishes immediately when the charge-energy gap obtained from the scaling with $1/N→ 0$ vanishes, constituting a finite-system version of the Mott transition. Analytic derivations of the formulas expressing either charge or spin concurrence in terms of ground-state correlation functions are also provided.